Transcutaneous Electrical Acupoint Stimulation Decreases the Incidence of Postoperative Nausea and Vomiting After Laparoscopic Non-gastrointestinal Surgery: A Multi-Center Randomized Controlled Trial - Gao, Wei; Zhang, Linzhong; Han, Xuechang; Wei, Lai; Fang, Jie; Zhang, Xiaqing; Zhang, Jiaqiang; Wang, Haiyun; Zhou, Qi; Wang, Chenggang; Chen, Wenting; Ni, Xinli; et al. (Frontiers in Medicine, 2022)
IMPORTANCE Postoperative nausea and vomiting (PONV) gives bad patient’s experience and negates patient’s good recovery from surgery. OBJECTIVE This trial aims to assess the preventive effectiveness of transcutaneous electrical acupoint stimulation (TEAS) on the incidence of PONV in high-risk surgical patients. DESIGN The large sample size, multicenter, evaluator-blinded, and randomized controlled study were conducted between September 3, 2019 to February 6, 2021. SETTING The 12 hospitals from different Chinese provinces PARTICIPANTS After obtained Ethics approval and written informed consent, 1,655 patients with Apfel score ≥ 3 points were enrolled for selective laparoscopic non-gastrointestinal surgery under general anesthesia. INTERVENTIONS Patients were randomly allocated into the TEAS and Sham group with 1:1 ratio. The TEAS group was stimulated on bilateral Neiguan and Zusanli acupoints after recovery from anesthesia on the surgical day and the next morning for 30 min, while the Sham group received an identical setting as TEAS but without currents delivered. Electronic patient self-reported scale was used to evaluate and record the occurrence of PONV. MAIN OUTCOMES AND MEASURES Primary clinical end point is the incidence of PONV which was defined as at least once nausea, retching or vomiting after operation within postoperative 24 h. RESULTS Compared with the Sham treatment, the TEAS lowered the PONV incidence by 4.8% (29.4% vs 34.2%, P = 0.036), and vomiting incidence by 7.4% (10.4% vs 17.8%, P < 0.001). TEAS also lowered persistent nausea incidence and PONV scores, decreased PONV related complications and Quality of Recovery–40 scores (P < 0.05). TEAS lowered the 24h PONV risk by 20% (OR, 0.80, 95% CI, 0.65 –0.98; P = 0.032), and lowered hazard ratio by 17% (HR, 0.83, 95% CI, 0.70–0.99; P = 0.035). Both TEAS and palonosetron were the independent PONV risk protective factors for 24 h PONV incidence and cumulative PONV incidence. The combination of TEAS and palonosetron was the most strategy to reduce the PONV incidence (P < 0.001). CONCLUSIONS AND RELEVANCE TEAS attenuated the PONV incidence and severity in high-risk surgical patients and may be applied clinically as a complement therapy to prevent PONV.